Perceived Value as a Mediating Variable in the Theory of Planned Behavior: Application to the Intention of Completing an Master of Business Administration - Yanina S. Bajana Villagomez; Sergio J. ChiÃ³n ChacÃ³n (International Review of Management and Marketing, 2020)
The objective of this research is to evaluate the intention to carry out an MBA in the Ecuadorian context through the model proposed by Azjen (1991); including the perceived value; as a mediating variable among the constructs (attitude, subjective norms and perceived behavioral control) and intention. The research was framed in a quantitative perspective, with a cross section. The estimation of the model was made, through the multivariate statistical technique of structural equations, in order to evaluate the relationships between constructs. The analyzed population were undergraduate students from all the Universities of Ecuador, of which a sample of 756 students was surveyed. It was evident that all the hypothetical relationships established in the proposed model are significant with respect to the intention to carry out an MBA. The perceived value for completing an MBA influences the intention to complete an MBA by 0.894. Likewise, the perceived value was evaluated as a mediating variable, concluding in accordance with what was proposed by Ato and Vallejo (2011), which meets the different processes for verification. Finally, the correlations between attitude, subjective norms and control perception were reported to be significant. In addition, the R2 of the dependent variables was determined, hence, the intention to carry out an MBA reported 79.9%; Similarly, the perceived value was determined, obtaining 65.5%.